Wolbachia endosymbionts subvert the endoplasmic reticulum to acquire host membranes without triggering ER stress. - Nour Fattouh; Chantal Cazevieille; Frédéric Landmann (Public Library of Science (PLoS), 2019)
The reproductive parasites Wolbachia are the most common endosymbionts on earth, present in a plethora of arthropod species. They have been introduced into mosquitos to successfully prevent the spread of vector-borne diseases, yet the strategies of host cell subversion underlying their obligate intracellular lifestyle remain to be explored in depth in order to gain insights into the mechanisms of pathogen-blocking. Like some other intracellular bacteria, Wolbachia reside in a host-derived vacuole in order to replicate and escape the immune surveillance. Using here the pathogen-blocking Wolbachia strain from Drosophila melanogaster, introduced into two different Drosophila cell lines, we show that Wolbachia subvert the endoplasmic reticulum to acquire their vacuolar membrane and colonize the host cell at high density. Wolbachia redistribute the endoplasmic reticulum, and time lapse experiments reveal tight coupled dynamics suggesting important signalling events or nutrient uptake. Wolbachia infection however does not affect the tubular or cisternal morphologies. A fraction of endoplasmic reticulum becomes clustered, allowing the endosymbionts to reside in between the endoplasmic reticulum and the Golgi apparatus, possibly modulating the traffic between these two organelles. Gene expression analyses and immunostaining studies suggest that Wolbachia achieve persistent infections at very high titers without triggering endoplasmic reticulum stress or enhanced ERAD-driven proteolysis, suggesting that amino acid salvage is achieved through modulation of other signalling pathways.